Analisis Perbandingan Profitabilitas Perusahaan Jasa Sebelum dan Selama Pandemi COVID-19 - Rahmadani, Rahmadani (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This paper aims to find out how significant the comparison of company profitability is before and during the Covid-19 pandemic.The population in this study were all companies in the hospitality industry, restaurant and tourism sub-sector listed on the Indonesia Stock Exchange (BEI) for the period 2019 - 2020. The sample in this study used the purposive sampling method, namely companies that had complete financial reports for the 3rd quarter of 2019 and Quarter 3 of 2020, the number of samples of this study were 31 companies. The results prove that the Gross Profit Margin (GPM), Net Profit Margin (NPM), Operating Profit Margin (OPM), and Return On Asset (ROA) tested with the test wicoxon have a significant effect on the Covid-19 pandemic on GPM, NPM, OPM and ROA. The Return On Equity (ROE) analyzed using the mann whitney also experienced significant differences before and during the Covid-19 pandemic. That way there is a significant difference in company profitability as measured by GPM, NPM, OPM, ROA, and ROE, the hospitality industry, restaurants and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX) before the Covid-19 pandemic and during the Covid-19 pandemic. It is hoped that this research can help investors and interested parties in responding to the Covid-19 pandemic.